All Days 2014
DOI: 10.2118/168632-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Various Fracture Fluid Systems Used in Multi-Stage Fractured Horizontal Wells: Montney Formation, Unconventional Gas

Abstract: Recently, there has been discussion of the need to advance hydraulic fracturing technology from the current ‘operational effectiveness’ mode of high-rate slickwater fracture designs, to a ‘fracture effectiveness’ mode provided by optimizing designs to achieve higher recoveries and better economics. This case study shows how advanced fracture fluid system designs have increased fracture effectiveness in an area of the Montney unconventional gas play. The study focused on fifty multi-stage fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…32 Membrane separation was selected as the current state-of-the-art process for removing CO 2 from CH 4 streams with low levels of liquid hydrocarbons. 27,51 The present model assumes 3 days for flaring prior to separation as recommended by industry experts. As membranes and other technologies advance, limitations due to mixed fluid quality and the associated requirement to initially vent both CH 4 and CO 2 could be reduced.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…32 Membrane separation was selected as the current state-of-the-art process for removing CO 2 from CH 4 streams with low levels of liquid hydrocarbons. 27,51 The present model assumes 3 days for flaring prior to separation as recommended by industry experts. As membranes and other technologies advance, limitations due to mixed fluid quality and the associated requirement to initially vent both CH 4 and CO 2 could be reduced.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Successful hydraulic fracturing treatment is the key to develop Montney formation since it has ultra-low permeability (~0.001mD) and it is sensitive to water. Energized fracturing including N 2 and CO 2 energized fracturing is more and more utilized in this formation (Burke & Nevison, 2011;Reynolds, Bachman, & Peters, 2014;Taylor, Fyten, & Romanson, 2010). Statistical analysis has shown that energized fractured wells gain much higher production than those of the non-energized fractured wells in the same area (Burke & Nevison, 2011).…”
Section: Case Study: Montney As Examplementioning
confidence: 99%
“…of natural gas liquids, and 136.3 billion bbl. of oil (P50 estimate) and the estimate of natural gas resources in British Columbia is 450 Tcf (Reynolds, Bachman, 2014). The Montney strata consist of interbedded fine grained sandstones, siltstone and dark grey shale and can be divided into upper, middle and lower units.…”
Section: Field Backgroundmentioning
confidence: 99%